1981
DOI: 10.1073/pnas.78.10.6266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vinblastine on distribution of murine leukemia virus-derived membrane-associated antigens.

Abstract: The effect of vinblastine on the distribution of murine leukemia virus-derived membrane-associated antigens was examined by using the indirect immunofluorescence of 3.7%formaldehyde-fixed MJD-54 (Moloney murine leukemia virus-infected) cells. On fixed, non-drug-treated cells, p30 antigen was distributed homogeneously and diffusely over the cell membrane.When cells were incubated with 10 pAM vinblastine for 1 hr before fixation, the distribution of p30 antigen was greatly changed, fluorescence now being collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The initial objectives of the present study were to determine if the modification and/or destruction of cytoskeletal elements could hinder or inhibit the production of infectious virus particles. Several precedents exist for this sort of interaction between cytoskeletal elements and virus replication pathways (Richardson & Vance 1978;Banes & Coleman 1980;Satake, McMillan & Luftig 1981;Volkman, Goldsmith & Hess 1987;Volkman 1988;Volkman & Zaal 1990;Hammonds, Denyer, Jackson & Irving 1996). In this study, the present authors demonstrate that intact microtubules and/or vimentin filaments are required for the proper distribution of CCV antigen.…”
Section: Discussionsupporting
confidence: 60%
“…The initial objectives of the present study were to determine if the modification and/or destruction of cytoskeletal elements could hinder or inhibit the production of infectious virus particles. Several precedents exist for this sort of interaction between cytoskeletal elements and virus replication pathways (Richardson & Vance 1978;Banes & Coleman 1980;Satake, McMillan & Luftig 1981;Volkman, Goldsmith & Hess 1987;Volkman 1988;Volkman & Zaal 1990;Hammonds, Denyer, Jackson & Irving 1996). In this study, the present authors demonstrate that intact microtubules and/or vimentin filaments are required for the proper distribution of CCV antigen.…”
Section: Discussionsupporting
confidence: 60%
“…In the case of alphaviruses, evidence for interactions between envelope and core proteins has been obtained by crosslinking studies (2), and recently it was shown that the nucleocapsid of Semliki Forest virus could interact in vitro with the cytoplasmic domain of the envelope protein p62/E2 (3). The transmembrane protein (pl5E) and the matrix protein (p15) of Moloney murine leukemia virus appeared to be colocalized at the plasma membrane of infected cells as determined by immunofluorescence (4,5), and the transmembrane glycoprotein (gp35) and matrix protein (p19) of Rous sarcoma virus were shown to be closely associated by chemical crosslinking analysis (6). Altered processing of the cytoplasmic domain of the Mason-Pfizer monkey virus glycoprotein was found recently in matrix protein mutants of this virus (35).…”
mentioning
confidence: 99%